The EFFECT OF BARANGAN BANANA STEM FIBER ON WATER SORPTION OF HEAT-CURED ACRYLIC RESIN - Sefty Aryani Harahap; Astrid Yudhit; Febby Chintya Andri (Jurnal Material Kedokteran Gigi, 2021)
Abstract Background: Water sorption is one of the properties of a material that can cause dimensional changes of heat cured acrylic resin which is used as a base for dentures and can affect the denture stability causing discomfort in the mouth. Objective: To determine the water sorption of heat cured acrylic resin after adding 0.5%, 1%, and 1.5% of Barangan banana stem fiber. Methods: 32 specimens were disk-shaped (n = 8) heat cured acrylic resin with a diameter of 50 mm and a thickness of 0.5 mm divided into 4 groups, namely group I as a control (without the addition of barangan banana stem fiber), group II (with the addition of 0.5% barangan banana stem fiber), group III (with the addition of 1% barangan banana stem fiber), and group IV (with the addition of 1.5% barangan banana stem fiber), then the water sorption value was calculated using the formula from the International Standards Organization No. 1567.. The data obtained were analyzed statistically. Results: The water sorption value obtained using the Kruskal-Wallis test followed by the Mann-Whitney test (p <0.05) was higher in heat cured acrylic resin with the addition of barangan banana stem fiber than the control group except for the addition of 0.5% barangan banana stem fiber. Conclusion: The addition of barangan banana stem fiber affects the water sorption value of heat cured acrylic resin. The more fiber added, the higher the water sorption of heat cured acrylic resin. Key words: Barangan banana stem fiber, heat cured acrylic resin, water sorption